2018
DOI: 10.1177/1120700018813547
|View full text |Cite
|
Sign up to set email alerts
|

The effect of conjoint tendon release on gait after direct anterior total hip arthroplasty

Abstract: Introduction: There has been considerable interest in the direct anterior (DA) approach to total hip arthroplasty (THA) recently. To facilitate exposure of the proximal femur it is sometimes necessary to release the conjoint tendon. Aim: To prospectively investigate whether release of the conjoint tendon has an impact on gait in the early postoperative period. Methods: We measured gait velocity, stride length, single-limb support and single-limb support symmetry preoperatively, at discharge from the hospital, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
(37 reference statements)
2
5
0
Order By: Relevance
“…Second, the authors criticize our lack of information on electrocautery denervation of the unresurfaced patella, and reference both their personal experience and the 2011 randomized trial by van Jonbergen et al [1] as evidence of this procedure's efficacy. However, van Jonbergen's later report on the same cohort found no difference in the incidence of anterior knee pain, as did 2 other randomized controlled trials [2,3] and a recent meta-analysis [4]. We believe the efficacy of this procedure is controversial at best.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Second, the authors criticize our lack of information on electrocautery denervation of the unresurfaced patella, and reference both their personal experience and the 2011 randomized trial by van Jonbergen et al [1] as evidence of this procedure's efficacy. However, van Jonbergen's later report on the same cohort found no difference in the incidence of anterior knee pain, as did 2 other randomized controlled trials [2,3] and a recent meta-analysis [4]. We believe the efficacy of this procedure is controversial at best.…”
mentioning
confidence: 71%
“…First, they suggest our length of follow-up was inadequate. In fact, for the 31,956 total knee arthroplasty (TKA) procedures included in our study, the mean follow-up was 7.3 years (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Given the mean time to secondary patella resurfacing (SPR) was 3.8 years, a longer follow-up would not alter our findings.…”
mentioning
confidence: 99%
“…Although the deep external rotators have been proposed as key active stabilizers of the hip described as the ‘rotator cuff’ of the hip [ 8 ], the CERT release during the DAA in THA has no impact on gait or patient-reported outcomes within the 12-week period post-surgery [ 23 ]. Yao et al investigated the outcome of DAA for THA and showed that the CERT release was not predictive of the length of stay, one year inpatient pain medication requirements, or outcome scores [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…For exposure of the proximal femur, many scholars have reported different methods to prevent femoral fracture [ 29 , 30 ]. After 3 years of practice, the authors have gained their own experience in releasing the proximal femur.…”
Section: Discussionmentioning
confidence: 99%